Exploring the dynamic relationships between risk perception and behavior in response to the Coronavirus Disease 2019 (COVID-19) outbreak. (September 2021) - Qin, Hua; Sanders, Christine; Prasetyo, Yanu; Syukron, Muh.; Prentice, Elizabeth
Abstract: The relationships between risk perception and related behavior form a fundamental theme in risk analysis. Despite increasing attentions on the temporal dimension of risk perception and behavior in recent literature, the dynamic relationships between these two constructs remain understudied. Infectious disease outbreaks, such as the Coronavirus Disease 2019 (COVID-19) pandemic, provide a key setting for analyzing evolving perceptions of and responses to natural or human-induced hazards. The main objectives of this research are: (1) to assess temporal changes in cognitive and affective dimensions of perceived COVID-19 risk as well as related protective behavior; and (2) to explore the dynamic relationships between COVID-19 risk perception and behavioral responses. Timely data on changing risk perception and behavior related to the COVID-19 outbreak were collected through two series of online surveys from four major cities (Seattle, Los Angeles, Chicago, and New York City; N  = 736) and the central Midwest region of the United States ( N  = 1240) respectively during March–August 2020. The analysis revealed that: (1) the cognitive and affective dimensions of perceived COVID-19 risk and preventive behavior all changed over time; (2) there were both within- and across-time correlations between COVID-19 risk perception indicators and preventive actions; and (3) preventive actions showed varied feedback effects on individual aspects of perceived COVID-19 risk over time. Findings from this research support and expand major conceptual approaches to changing relationships between risk perception and behavior, particularly the risk reappraisal hypothesis. The study also has useful implications for health risk management and future research directions. Highlights: The research included two separate case studies with similar methods and designs. We tested the accuracy, behavior motivation, and risk reappraisal hypotheses. Risk perception and behavior in response to COVID-19 changed over time. Reduced path models included within- and across-time correlations between them. There was an interaction effect between actions and study phase on risk perception.